Characterization and Genetic Relationships of Vibrio spp. Isolated from Seafood in Retail Markets, Yala, Thailand - Preeprem, Sutima; Aksonkird, Titita; Nuidate, Taiyeebah; Hajimasalaeh, Warunee; Hajiwangoh, Zubaidah; Mittraparp-arthorn, Pimonsri (Trends in Sciences, 2023)
Vibrio spp. including Vibrio cholerae and V. parahaemolyticus are the major causative agent of diarrhea involved in seafood consumption. Yala is a southern border province in Thailand where no seafood sources are provided. Thus, it is necessary to import several seafood products from neighboring provinces. The risk of Vibrio spp. replication is increased during seafood transport. Therefore, the objectives of this study were to isolate and characterize V. cholerae and V. parahaemolyticus from seafood in Yala and to investigate their genetic relationships with virulent and clinical strains. A total of 100 Vibrio isolates were obtained from four different sample types in retail markets. It was found that two-thirds of all isolates were yellow colonies on TCBS agar. Using PCR with specific primers, 34 % of V. cholerae and 8 % of V. parahaemolyticus were identified. To classify the virulence strains, Vibrio spp. were positive for hlyA and tdh, 17 and 1 %, respectively. Moreover, 54 % of Vibrio isolates were able to produce biofilm and 28 % of those isolates showed a high level of biofilm production. All representative strains of V. cholerae presented ß-hemolysin on blood agar correlated to hlyA while representative strains of V. parahaemolyticus presented γ-hemolysin and ß-hemolysin on blood agar. In addition, ERIC-PCR provided different DNA profiles of representative V. cholerae and V. parahaemolyticus which some strains showed a correlation with clinical strains and virulent strains. Therefore, these findings might indicate the risk of Vibrio infections for seafood consumers, especially in Yala province where seafood needs to be imported from other provinces. HIGHLIGHTS The first report showed high risk of Vibrio cholerae and V. parahaemolyticus spread in non-seafood source area: Yala province The majority of Vibrio cholerae and V. parahaemolyticus isolated from seafood in retail markets, Yala, Thailand was classified as virulent strains which possess major virulence genes, hemolytic activity, and biofilm formation Several Vibrio isolates obtained from seafood showed genetic similarities with virulent and clinical strains GRAPHICAL ABSTRACT